Transformasi Visual dan Makna Simbolik Motif Batik Parang Rusak dalam Konteks Budaya Modern - Nan Quddus, Sang Padi; Cahyana, Agus; Falah, Asep Miftahul; Nagara, Martien Roos (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
The Parang Rusak batik motif is one of Indonesia’s classical cultural heritages, originating from the Javanese royal courts and rich in philosophical values, such as strength, resilience, and the spirit of life’s struggle. Over time, this motif has undergone transformation not only in its visual form but also in its symbolic meaning, especially within the context of commercialization and adaptation in the modern creative industry. This study aims to analyze the transformation of both form and meaning in the Parang Rusak motif, with a particular focus on the works of Batik Hasan Bandung. Employing semiotic and historical approaches, this research explores how traditional motifs are creatively modified while preserving their philosophical essence. The findings reveal that Batik Hasan successfully sustains the symbolic meaning of the Parang Rusak motif through visual innovation that remains rooted in traditional principles. This transformation serves as an example of dynamic cultural adaptation, where the preservation of noble values can coexist with contemporary demands and creative evolution. This study contributes to strengthening public appreciation of batik as a living and evolving symbol of Indonesian cultural identity.